Probability Mapping for Mycoplasma gallisepticum Risk in Backyard Chickens in Paraguay - Herrero, M.; Suzuki, K.; Origlia, J.; Nunez, L.; Faccioli, M.; Silva, M.; Caballero, J.; Valiente, O.; Alvarez, F. (International Journal of Poultry Science, 2009)
Poultry production is a growing industry in Paraguay, South America. The insufficient farm management methods commonly used in backyard chickens make them a potential reservoir for economically important diseases such as Mycoplasma gallisepticum that can influence commercial poultry operations. There are no previous studies on a survey of Mycoplasma gallisepticum among backyard chicken population in Paraguay. The objectives of this study were: (a) to determine the seroprevalence of Mycoplasma gallisepticum in backyard chickens in Paraguay and (b) to generate choropleth maps for the Standardized Risk Ratio (SRR) for Mycoplasma gallisepticum in the study chickens and Poison probabilities for the SRR, in place of using the raw seroprevalence. Paraguay is divided into 17 departments. A department-stratified random sampling was planned and conducted. The required total sample size of 1291 from a chicken population of 17 million was sufficient to produce a 95% confidence interval with a desired precision of ±2.5% when the estimated antibody seroprevalence was 30%. Sera were analyzed using a commercial indirect ELISA. The observed overall seroprevalence was 26%. The resulting maps for the SRR for Mycoplasma gallisepticum in the study chickens at department level and Poison probabilities for the SRR were depicted. Departments with significantly high or low disease risks were confirmed. Different types of epidemiological parameters can be calculated to take account of potential risk factors. Therefore, further detailed investigations into those risk factors associated with Mycoplasma gallisepticum occurrence with respect to spatially epidemiological differences would be of interest.